To solve the expression (-2/3) x (-3) ÷ (-6/11) x (3/4), we can simplify each component separately and then perform the division and multiplication.
First, let's simplify (-2/3) x (-3):
(-2/3) x (-3) = (2/3) x (3) = 6/3 = 2
Next, let's simplify (-6/11) x (3/4):
(-6/11) x (3/4) = (-18/44) = (-9/22)
Then, let's perform the division: 2 ÷ (-9/22)
Dividing by a fraction is the same as multiplying by its reciprocal, so we have:
(2/1) x (22/-9) = (-44/9)
Therefore, the expression (-2/3) x (-3) ÷ (-6/11) x (3/4) simplifies to -44/9, which can also be written as -4 8/9.
Use the properties of operations and rules for multiplying and dividing signed numbers to solve:
*
1 point
(-2/3) x (-3) divided by (-6/11) x (3/4)
2 3/4
-2 3/4
81/99
-81/99
1 answer